Prevalence and treatment of allergies in rural areas of Bavaria, Germany: a cross-sectional study - Danielle Boehmer; Barbara Schuster; Julia Krause; Ulf Darsow; Tilo Biedermann; Alexander Zink (World Allergy Organization Journal, 2018)
Abstract Background There is a high prevalence of allergies in Germany, with approximately 20% of the population having at least one allergy and only about 10% of these being treated adequately. We conducted a cross-sectional study in a rural area of Bavaria (Southern Germany) to evaluate the prevalence of allergies and their treatment, because research regarding this topic is currently limited. Methods Data were collected in 10 offices of non-dermatological doctors using a self-filled questionnaire to ask participants about allergies and treatment. Results A total of 641 questionnaires were appropriate for analysis. The prevalence of allergies in the Bavarian countryside was higher than that reported for Germany (37.3% vs. 20.0%). Furthermore, almost a third (30.4%) of allergies were not treated at all. The most frequently consulted therapist was found to be a general practitioner. Conclusions Based on the study results, there is a need for prevention programs and establishment of treatments for certain allergies to minimize long-term health effects. Moreover, more studies are needed to analyze the prevalence of allergies in farmers who had a higher prevalence of allergies compared to previously reported prevalence in literature reviews. Trial registrations The study was approved by the ethical review committee of the Technical University Munich (EC number 548/16S).